X-linked adrenoleukodystrophy and primary adrenal insufficiency - Cappa, Marco; Todisco, Tommaso; Bizzarri, Carla (Frontiers in Endocrinology, 2023)
X-linked adrenoleukodystrophy (X-ALD; OMIM:300100) is a progressive neurodegenerative disorder caused by a congenital defect in the ATP-binding cassette transporters sub-family D member 1 gene (ABCD1) producing adrenoleukodystrophy protein (ALDP). According to population studies, X-ALD has an estimated birth prevalence of 1 in 17.000 subjects (considering both hemizygous males and heterozygous females), and there is no evidence that this prevalence varies among regions or ethnic groups. ALDP deficiency results in a defective peroxisomal β-oxidation of very long chain fatty acids (VLCFA). As a consequence of this metabolic abnormality, VLCFAs accumulate in nervous system (brain white matter and spinal cord), testis and adrenal cortex. All X-ALD affected patients carry a mutation on the ABCD1 gene. Nevertheless, patients with a defect on the ABCD1 gene can have a dramatic difference in the clinical presentation of the disease. In fact, X-ALD can vary from the most severe cerebral paediatric form (CerALD), to adult adrenomyeloneuropathy (AMN), Addison-only and asymptomatic forms. Primary adrenal insufficiency (PAI) is one of the main features of X-ALD, with a prevalence of 70% in ALD/AMN patients and 5% in female carriers. The pathogenesis of X-ALD related PAI is still unclear, even if a few published data suggests a defective adrenal response to ACTH, related to VLCFA accumulation with progressive disruption of adrenal cell membrane function and ACTH receptor activity. The reason why PAI develops only in a proportion of ALD/AMN patients remains incompletely understood. A growing consensus supports VLCFA assessment in all male children presenting with PAI, as early diagnosis and start of therapy may be essential for X-ALD patients. Children and adults with PAI require individualized glucocorticoid replacement therapy, while mineralocorticoid therapy is needed only in a few cases after consideration of hormonal and electrolytes status. Novel approaches, such as prolonged release glucocorticoids, offer potential benefit in optimizing hormonal replacement for X-ALD-related PAI. Although the association between PAI and X-ALD has been observed in clinical practice, the underlying mechanisms remain poorly understood. This paper aims to explore the multifaceted relationship between PAI and X-ALD, shedding light on shared pathophysiology, clinical manifestations, and potential therapeutic interventions.